No judgment : essays - Oyler, Lauren (HarperOne, an imprint of HarperCollins Publishers, 2024)
"In her writing for Harper's, the London Review of Books, The New Yorker, and elsewhere, Lauren Oyler has emerged as one of the most trenchant and influential critics of her generation, a talent whose judgments on works of literature--whether celebratory or scarily harsh--have become notorious. But what is the significance of being a critic and consumer of media in today's fraught environment? How do we understand ourselves, and each other, as space between the individual and the world seems to get smaller and smaller, and our opinions on books and movies seem to represent something essential about our souls? And to put it bluntly, why should you care what she--or anyone--thinks? In this, her first collection of essays, Oyler writes ... about topics like the role of gossip in our exponentially communicative society, the rise and proliferation of autofiction, why we're all so 'vulnerable' these days, and her own anxiety" --